Validation of Reliable Reference Genes for RT-qPCR Studies of Target Gene Expression in Colletotrichum camelliae During Spore Germination and Mycelial Growth and Interaction With Host Plants - He, Shengnan; An, Tai; A, Runa; Liu, Shouan (Frontiers in Microbiology, 2019)
The tea plant [Camellia sinensis (L.) O. Kuntze] is one of the most important leaf crops, and it is widely used for the production of non-alcoholic beverages worldwide. Tea also has a long history of medicinal use. Colletotrichum camelliae Massee is one of the dominant fungal pathogens that infects tea leaves and causes severe tea anthracnose disease. To analyse the molecular biology of C. camelliae, the quantification of pathogen gene expression by the RT-qPCR method is necessary. Reliable RT-qPCR results require the use of stable reference genes for data normalization. However, suitable reference genes have not been reported in C. camelliae thus far. In this study, 12 candidate genes (i.e., CcSPAC6B12.04c, CcWDR83, Cchp11, Ccnew1, CcHplo, CcRNF5, CcHpcob, CcfaeB-2, CcYER010C, CcRNM1, CcUP18 and CcACT) were isolated from C. camelliae and assessed as potential reference genes. The expression stability of these genes in C. camelliae during spore germination and mycelial growth and interaction with host plants was first evaluated using several statistical algorithms, such as geNorm, NormFinder, and Bestkeeper. A web-based analysis program, Refinder, was then used to find the most suitable reference genes. Our results indicated that Cenew1, CcHplo and CcSPAC6B12.04c were the most stable reference genes in C. camelliae under all conditions. Our work provided the most suitable reference genes for future studies performed to quantify the target gene expression levels of C. camelliae.